Irish milkshake murder - O'Connor, Carlene; Ehrhart, Peggy; Ireland, Liz (Kensington Publishing Corp., 2024)
Three cozy novellas that take place on St. Patrick's Day include the tale of a killer green milkshake at a New Jersey luncheonette and another murderous milkshake that takes out a wedding guest on a ferry trip to Inis Mór.